Configuration research on innovation performance of digital enterprises: Based on an open innovation and knowledge perspective - Dong, Hao; Guo, Ju’e; Chen, Tianqing; Murong, Ruiyi (Frontiers in Environmental Science, 2023)
Based on the perspective of open innovation and knowledge, this paper constructs a driving mechanism model for the innovation performance of digital enterprises and then uses 36 digital enterprises as research samples to reveal the impact of different paths of knowledge integration capability, open innovation and knowledge sharing on innovation performance. The results show that:(1) digital enterprises can promote innovation performance through a balanced drive model of "knowledge integration capability-open innovation-knowledge sharing", a dual drive model of "knowledge integration capability-open innovation" and a dual drive model of "knowledge integration capability-knowledge sharing";(2) Different knowledge integration capabilities can all promote to innovation performance;(3) knowledge sharing improves the management and utilization of knowledge, which is an important guarantee for improving innovation performance. Finally, the paper discusses the results, and puts forward some management suggestions, such as actively matching open innovation, moderately developing knowledge integration capabilities, and improving the ability of knowledge sharing.